Multi-omics analysis reveals changes in tryptophan and cholesterol metabolism before and after sexual maturation in captive macaques - Xu Liu; Xuyuan Liu; Xinqi Wang; Ke Shang; Jiawei Li; Yue Lan; Jiao Wang; Jing Li; Bisong Yue; Miao He; Zhenxin Fan (BMC Genomics, 2023)
Abstract Rhesus macaques (Macaca mulatta, RMs) are widely used in sexual maturation studies due to their high genetic and physiological similarity to humans. However, judging sexual maturity in captive RMs based on blood physiological indicators, female menstruation, and male ejaculation behavior can be inaccurate. Here, we explored changes in RMs before and after sexual maturation based on multi-omics analysis and identified markers for determining sexual maturity. We found that differentially expressed microbiota, metabolites, and genes before and after sexual maturation showed many potential correlations. Specifically, genes involved in spermatogenesis (TSSK2, HSP90AA1, SOX5, SPAG16, and SPATC1) were up-regulated in male macaques, and significant changes in gene (CD36), metabolites (cholesterol, 7-ketolithocholic acid, and 12-ketolithocholic acid), and microbiota (Lactobacillus) related to cholesterol metabolism were also found, suggesting the sexually mature males have stronger sperm fertility and cholesterol metabolism compared to sexually immature males. In female macaques, most differences before and after sexual maturity were related to tryptophan metabolism, including changes in IDO1, IDO2, IFNGR2, IL1Β, IL10, L-tryptophan, kynurenic acid (KA), indole-3-acetic acid (IAA), indoleacetaldehyde, and Bifidobacteria, indicating that sexually mature females exhibit stronger neuromodulation and intestinal immunity than sexually immature females. Cholesterol metabolism-related changes (CD36, 7-ketolithocholic acid, 12-ketolithocholic acid) were also observed in female and male macaques. Exploring differences before and after sexual maturation through multi-omics, we identified potential biomarkers of sexual maturity in RMs, including Lactobacillus (for males) and Bifidobacterium (for females) valuable for RM breeding and sexual maturation research.